ANALISIS TERHADAP PENGAWASAN KEWENANGAN KOMISI PEMBERANTASAN KORUPSI (KPK) OLEH DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA (DPR RI) SEBAGAI PERWUJUDAN PRINSIP CHECKS AND BALANCES - Manalu, Josua Victor; Firdausy, Adriana G. (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This study analyze the Authority Supervision of Corruption Eradication Commission (KPK) by The House of Representatives of The Republic of Indonesia (DPR RI) as an Embodiment The Principles of Checks and Balances: What are the obstacles that occur in authority supervision of KPK by DPR RI? How does the ideal supervision of the KPK’s authority by DPR RI as an embodiment of The Principles of Checks and Balances? The purpose of this research is to know the problems that occur in the supervision of the KPK’s authority by DPR RI in a more concrete manner and to know the ideal supervision of the KPK’s authority by DPR RI as the embodiment of the principle of checks and balances. This research is normative, prescriptive, and applied legal research. The approach used is the conceptual approach. Legal materials collection technique used is the study of literature. KPK is a state agency which in carrying out its duties and authority is independent and free from any influence of power. KPK is a state agency that was born as part of the executive department with the aim to eradicate corruption in Indonesia. The position of the KPK in the Indonesian state administration system that exists in the executive domain becomes the basis that DPR RI’s supervision over the KPK can be done because KPK is included in the object of the right of inquiry from DPR RI. Indonesia at present has embodied the principle of checks and balances as a manifestation of mutual balance and oversight among existing state institutions so that each state institution can work maximally in carrying out its functions, and to prevent the potential presence of arbitrariness of each the state institution. Supervision conducted by DPR RI to the KPK in accordance with the mandate of the existing constitution and ensure the implementation of the state by the state institutions in accordance with applicable law is through the right of inquiry, namely by providing recommendations to the KPK in order to strengthen and improve the performance of the KPK in the future.